Bibliometric Analysis of B2B Marketing in the Digital Age - Judijanto, Loso; Supriatna, Endang (West Science Interdisciplinary Studies, 2026)
This study aims to map and synthesize the intellectual structure, thematic evolution, and collaboration patterns of B2B marketing research in the digital age using a bibliometric approach. Drawing on peer-reviewed journal articles indexed in the Scopus database, the study employs VOSviewer to conduct citation analysis, co-word analysis, co-authorship analysis, and network visualization. The results reveal that digital marketing constitutes the central conceptual core of contemporary B2B marketing research, integrating technological, strategic, and relational dimensions. Thematic evolution analysis indicates a clear shift from early emphases on electronic commerce and information systems toward more recent focuses on artificial intelligence, digital platforms, social media marketing, customer engagement, and customer journey. Collaboration analysis further shows a globally interconnected yet uneven research landscape, with the United States and several European countries acting as dominant hubs of knowledge production. Overall, this study provides a comprehensive overview of how B2B marketing scholarship has evolved in response to digitalization and offers a structured foundation for future theoretical development and empirical research in digitally mediated B2B contexts⁠.